DIGITALIZATION OF THE PROCESS OF CITIZENS 'SERVICES AS USERS OF PUBLIC SERVICES IN THE FUNCTION OF ECONOMIC DEVELOPMENT - SITUATIONAL ANALYSIS OF THE REPUBLIC OF SERBIA (Heritage, 2021)
The Republic of Serbia has in recent years increased the number of public services that citizens electronically can receive from state institutions. The digitalisation of public administration is one of the priorities of the Republic of Serbia. Significant impacts of digitalisation are: increasing the transparency of the process, reduce corruption, reduce administrative costs, increase competitiveness and most importantly the process of digitization is in the function of economic development.
Keywords: digitalization, public services, economic development, government, ciтizens, communication, Republic of Serbia